Uma proposta metodológica para o ensino de óptica geométrica com o auxílio do software GeoGebra - Souza, Diogo Emerson de (2017)
Facing the students’ lack of motivation during Physics classes and the presence of new digital technologies that can aid and improve the teaching approach nowadays, this present work consists of proposing a methodology capable of promoting Geometric Optics learning, specifically for the Reflection theme, through the Geogebra software as a pedagogical resource. Based on the idea that computer simulations allow the development of several skills, involve concentration on the theoretical concepts and help to contextualize theory and practice, the official proposals (PCNs and Curriculum of the State of São Paulo) which aim to guide the teacher, indicating the necessary abilities that students must acquire when graduating high school were studied and investigated. A test was applied after the activities and we could verify a satisfactory result of the methodology.